Relationship between foraminifera and bacteria in estuarine sediments from Santa Catarina Island, Brazil - Laut, Lázaro L. M.; Silva, F. S.; Bonetti, C.; Figueiredo Jr, A.G.; Crapez, M. A. C. (Anuário do Instituto de Geociências, 2006)
Abstract